Rapid reshaping of the soil microbiome and metabolome during short-term flooding and draining in rice - Lu, Yanyao; Lai, Donghong; Cai, Shuo; Wang, Haiyuan; Hu, Zejun; Xiong, Qiangqiang (Frontiers in Microbiology, 2025)
The impact of the flooding-draining process on soil ecosystems is complex and dynamic. However, the specific effects of different drainage durations on soil microorganisms and metabolites remain unclear. This study adopted a multi-omics research method. After nontargeted metabolomics analysis of lipids as the main metabolite, microbial diversity analysis and lipidomics analysis were conducted to determine the main influencing factors. Subsequently, correlation analysis was performed with physiological and biochemical data to logically explore the changes in soil microorganisms and metabolites during the drainage process (Day 1 after drainage, R1; Day 2, R2; Day 3, R3; Day 4, R4; and Day 5, R5). The results revealed that S-PPO, S-POD, and S-CAT decreased with prolonged drainage time, whereas the soil redox potential (Eh-mV) and POD increased. Among the various postdrainage comparison groups, lipids and lipid-like molecules were the predominant metabolites. Among lipids, the TG subclass of glycerolipids (GLs) and the Cer subclass of sphingolipids (SPs) were the most abundant. The TG subclass was consistently present in the lipid correlation networks across all comparison groups, with TG (15:0/18:1/18:1) exhibiting significant differences between the R4 and R1 groups. Redox reactions involving lipids were associated mainly with triglycerides, with the most pronounced reduction observed on the second day postdrainage. The most pronounced lipid reduction reaction was observed on the second day after drainage. Notable differences in bacterial abundance were detected between the R4 and R5 groups. At the phylum level, the dominant bacterial communities primarily comprised Actinobacteriota and Chloroflexi, with the bacterial community structure being significantly influenced by drainage. The predominant fungal communities were composed of mainly Ascomycota and Rozellomycota. Actinobacteriota and triglyceride (TG) lipids were the major components affected during the drainage period. Correlations were identified among environmental factors, lipids, and microbial communities, indicating their cooperative interactions. The results of this study indicate that with the increase in water intake time, the redox reactions in soil lipids and the richness of bacterial communities in rice soil significantly increase. At the same time, rapid remodeling can have an impact on soil ecosystems, which helps to better understand the adaptation strategies of rice soil ecosystems under adversity.